An exploratory study on low-concentration hexavalent chromium adsorption by Fe(III)-cross-linked chitosan beads. Issue 11 (29th November 2017) - Wu, Yaoguo; Zhang, Yuanjing; Qian, Jin; Xin, Xu; Hu, Sihai; Zhang, Shuai; Wei, Jianguo
Abstract : In this study, Fe(III)-cross-linked chitosan beads (Fe(III)-CBs) were synthesized and employed to explore the characteristics and primary mechanism of their hexavalent chromium (Cr(VI)) adsorption under low concentration Cr(VI) (less than 20.0 mg l −1 ) and a pH range from 2.0 to 8.0. Batch tests were conducted to determine the Cr(VI) adsorption capacity and kinetics, and the effects of pH and temperature on the adsorption under low concentration Cr(VI) and a pH range from 2.0 to 8.0. Scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy were employed to explore the characteristics of Fe(III)-CBs and their Cr(VI) adsorption mechanisms. The results show that, unlike the adsorption of other absorbents, the Cr(VI) adsorption was efficient in a wide pH range from 2.0 to 6.0, and well described by the pseudo-first-order model and the Langmuir–Freundlich isotherm model. The capacity of Cr(VI) adsorption by Fe(III)-CBs was as high as 166.3 mg g −1 under temperature 25°C and pH 6.0. The desorption test was also carried out by 0.1 mol l −1 NaOH solution for Fe(III)-CBs regeneration. It was found that Fe(III)-CBs could be re-used for five adsorption–desorption cycles without significant decrease in Cr(VI) adsorption capacity. Ion exchange was confirmed between functional groups (i.e. amino group) and Cr(VI) anions (i.e. CrO 4 2 − ). The amino-like functional groups played a key role in Cr(VI) distribution on the Fe(III)-CBs surface; Cr(VI) adsorbed on Fe(III)-CBs was partially reduced to Cr(III) with alcoholic group served as electron donor, and then formed another rate-limiting factor. So, Fe(III)-CBs has a good prospect in purifying low concentration Cr(VI) water with a pH range from 2.0 to 6.0.